Legal Liability Of DPLK Manulife Indonesia Financial Institution On Pension Funds (Review Of Industrial Relations Dispute Decision Number 184/Pdt.Sus-PHI.G/2020/PN. JKT. PST) - Herry Suherman; Diana R.W. Napitupulu; Gindo L. Tobing (Jurnal Scientia, 2024)
Pension funds are principally legal entities formed to provide welfare guarantees to employees and allow employees to minimize risks arising from problems faced in old age and risks when they are no longer working in productive age. In principle, pension funds are one alternative to provide welfare guarantees to employees. The existence of welfare guarantees allows employees to minimize problems arising from risks that will be faced in the course of life, such as the risk of losing work, old age, and accidents that result in disability or even death. The type of research in this study is exploratory legal study, which is defined as basic legal research and aims to obtain information, information and data on matters that are not yet known regarding the legal liability of the Financial Institution Pension Fund (DPLK) in relation to the implementation of Industrial Relations Dispute (PHI) decisions. The research approach uses a normative research approach, namely an approach through library research by reading, quoting and analyzing legal theories and laws and regulations related to the issue of legal liability of the Financial Institution Pension Fund (DPLK) in relation to the implementation of Industrial Relations Dispute (PHI) decisions. In general, there are two pension plan benefit schemes, namely Defined Benefit (DB) and Defined Contribution (DC). In DB design, the amount of pension benefits is determined by a formula that is generally based on income, accrual rate, length of service, and/or period of employment. In its development, there are several modifications of the two programs with the most popular being the Non-financial/Notional Defined Contribution (NDC) scheme. This scheme allows benefits whose amount is recognized virtually (notional) and determined in advance. The company regulation explains that the company has reserved costs to anticipate layoffs through or by using DPLK. PHI Decision Number: 184/Pdt.Sus-PHI/2020/PN. JKT. PST, of course, has not been able to provide a sense of fairness to each party. The PHI decision can only emphasize the case of Termination of Employment and the amount of severance pay to be paid by the company, the company in this case can order DPLK MI to make severance payments with the provisions as contained in the applicable laws and regulations.